Redox- and pH-Responsive Polymersomes with Ferrocene Moieties Exhibiting Peroxidase-like, Chemoenzymatic Activity and H2O2-Responsive Release Behavior - Moreno, Silvia; Huebner, Hanna; Effenberg, Christiane; Boye, Susanne; Ramuglia, Anthony; Schmitt, Deborah; Voit, Brigitte; Weidinger, Inez M.; Gallei, Markus; Appelhans, Dietmar (Biomacromolecules, 2022)
The development of compartments for the design of cascade reactions in a local space requires a selective spatiotemporal control. The combination of enzyme-loaded polymersomes with enzymelike units shows a great potential in further refining the diffusion barrier and the type of reactions in nanoreactors. Herein, pH-responsive and ferrocene-containing block copolymers were synthesized to realize pH-stable and multiresponsive polymersomes. Permeable membrane, peroxidase-like behavior induced by the redox-responsive ferrocene moieties and release properties were validated using cyclovoltammetry, dye TMB assay, and rupture of host-guest interactions with β-cyclodextrin, respectively. Due to the incorporation of different block copolymers, the membrane permeability of glucose oxidase-loaded polymersomes was changed by increasing extracellular glucose concentration and in TMB assay, allowing for the chemoenzymatic cascade reaction. This study presents a potent synthetic, multiresponsive nanoreactor platform with tunable (e.g., redox-responsive) membrane properties for potential application in therapeutics.
CRIS-Team Scopus Importer:2023-03-20